Odpowiedzi

2010-03-08T19:02:12+01:00
A) 2t-(3t+1)=6
2t-3t-1=6
-t=7
t=-7
b) -(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
c) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
0y=0
d) (x-7)-2(3x+5)=3
x-7-6x-10=3
-6x+x=20
-5x=20
-x=4
x=-4
liczę na naj ;]
Najlepsza Odpowiedź!
2010-03-08T19:04:07+01:00
A) 2t-(3t+1)=6
-t=5 /*-1
t=-5

b) -(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

c) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
0=0
równanie sprzeczne

d) (x-7)-2(3x+5)=3
x-7-6x-10=3
-5x=20 /-5
x=-4

2010-03-08T19:11:02+01:00
A) 2t-(3t+1)=6
2t-3t-1=6
2t-3t=6+1
-t=7/:(-1)
t=-7

b) -(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10


c) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0

d) (x-7)-2(3x+5)=3
x-7-6x-10=3
x-6x=3+7+10
-5x=20/:(-5)
x=-4

;))